2010
DOI: 10.5089/9781451982732.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth Convergence and Spillovers Among Indian States: What Matters? What Does Not?

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.Convergence and spillovers across countries and within countries are old, but recurrent policy concerns, and India is no exception to this rule. This paper examines convergence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The twin-peak observations from kernel plots and the findings from the transition matrices of our study support the claim of club-convergence process across the 15 major states. Bandyopadhyay (2004Bandyopadhyay ( , 2011, Ghosh (2008) and Sodsriwiboon and Kalra (2010) have explored the presence of two-club convergence of income across Indian states and our findings are found to be consistent with their studies; however, Chaudhuri, Mazumdar, Teachout, and Marimoutou (2007) have observed three peaks in their documentation of polarization using a different methodology based on regression tree approach.…”
Section: Empirical Findingssupporting
confidence: 88%
“…The twin-peak observations from kernel plots and the findings from the transition matrices of our study support the claim of club-convergence process across the 15 major states. Bandyopadhyay (2004Bandyopadhyay ( , 2011, Ghosh (2008) and Sodsriwiboon and Kalra (2010) have explored the presence of two-club convergence of income across Indian states and our findings are found to be consistent with their studies; however, Chaudhuri, Mazumdar, Teachout, and Marimoutou (2007) have observed three peaks in their documentation of polarization using a different methodology based on regression tree approach.…”
Section: Empirical Findingssupporting
confidence: 88%
“…Sodsriwiboon and Kalra (2010) have characterized a dynamic relationship for the high-, medium-, and low-income states of India through a system of equation. Each period of growth has been regressed with its own lag as well as the lag of the other two periods, taking into consideration of fixed effects of each group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rest of the state's agriculture and industry in the pre-reforms period have influence for Haryana, Gujarat, Himachal Pradesh, Tamil Nadu, Uttar Pradesh, Bihar, and Kerala, whereas, in the reform period, they have influence for Rajasthan, Maharashtra, Kerala, and Punjab. Sodsriwiboon and Kalra (2010) have characterized a dynamic relationship for the high-, medium-, and low-income states of India through a system of equation. Each period of growth has been regressed with its own lag as well as the lag of the other two periods, taking into consideration of fixed effects of each group.…”
Section: Literature Reviewmentioning
confidence: 99%